Model Manajemen Fundraising Wakaf Pada Yayasan Dana Sosial Al Falah (YDSF) Surabaya - Miftahul Huda (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2012)
Nazir autonomous and continuity is always needed to share out properties donated for religious or community use (wakaf product) continuously. This assumption actually needs wakaf’s properties and fund sources to increase fundraising model of wakaf. This article is to investigate fundraising model of wakaf trough conventional resources, assets productivity, and ”˜in-link’ of wakaf at YDSF Surabaya. The writer uses qualitative descriptive approach to seek the field data from a single case. Findings show that “Yayasan Dana Sosial al-Falah” (YDSF) Surabaya applies not only fundraising management of wakaf to improve resource fundraising model for collecting conventional resources but also grant fundraising to enrich wakaf distribution program. YDSF does not empower asset fundraising model yet, so it is at direct management cluster category.